Calcified carotid atherosclerotic plaques on digital panoramic radiographs in patients with Type II diabetes mellitus: A case control study - Neha Khambete; Rahul Kumar (Wolters Kluwer Medknow Publications, 2015)
Aim: Diabetes mellitus is associated with accelerated carotid artery atherosclerosis and increased risk of stroke. This study was conducted with the objective of determining the prevalence of calcified atherosclerotic plaques on panoramic radiographs of patients with Type II diabetes mellitus. Materials and Methods: Panoramic radiographs of 100 patients (age range 50-84 years) with known history of type II diabetes mellitus, visiting the outpatient department were evaluated for the presence of calcified atherosclerotic plaques. Age- and sex-matched controls were evaluated in the same manner. Statistical comparison of prevalence rates was done. Results: The radiographs of diabetics (mean age: 64.45 years) revealed that 26% had atheromatous plaques, whereas those of controls (mean age: 65.36 years) revealed that 6% had atheromatous plaques. A statistically significant difference (P = 0.01410) was obtained using Yates' Chi-square test. Conclusion: People with diabetes mellitus had a greater prevalence of calcified atherosclerotic plaques on panoramic radiographs than non-diabetics. Panoramic radiographs of diabetic patients should be screened for the presence of carotid artery atheromatous plaques for timely medical referral of asymptomatic patients and avoiding any further serious consequences like cerebrovascular accidents.